1978
DOI: 10.1093/bja/50.7.665
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Inhalation Anaesthetic Agents

Abstract: Although hundreds of compounds on the chemist's shelf are known to produce anaesthesia, relatively few are used clinically. The requirements for a clinically useful anaesthetic agent are necessarily stringent and include: a wide margin of safety, total reversibility of anaesthetic effect and an absence of long-term toxicity. In addition, a successful inhalation anaesthetic agent must combine the capacity for depression of the central nervous system with low levels of interference with respiration and the circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Solvents, as well as anesthetic agents, are fat-soluble, which is also one of the conditions for the narcotic effects. Besides, anesthetic gases can form toxic metabolites (15) in the same manner as many solvents; these metabolites react on the cellular level and can induce cell damage there (58). The chronic damage caused by solvents has been studied to a great extent during the last 10 a, and many studies have shown effects on the central nervous system as a consequence of long-term exposure to solvents (38).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Solvents, as well as anesthetic agents, are fat-soluble, which is also one of the conditions for the narcotic effects. Besides, anesthetic gases can form toxic metabolites (15) in the same manner as many solvents; these metabolites react on the cellular level and can induce cell damage there (58). The chronic damage caused by solvents has been studied to a great extent during the last 10 a, and many studies have shown effects on the central nervous system as a consequence of long-term exposure to solvents (38).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…45 In addition to its toxic effects on the liver, halothane also impairs hepatic hemodynamics. 46 Severe halothane hepatitis is seen in 1/6,000-1/35,000 patients administered halothane. Although repetitive applications are generally blamed, it has been reported even in the case of first exposure to a volatile anesthetic (39%).…”
Section: Relationship Between Anesthesia and Liver Functionsmentioning
confidence: 99%
“…This same research reports that the TFAA does not appear to block the Krebs cycle like the more toxic monofluoroacetic acid (Airaksinen, 1968). Research to date seem to confirm that TFAA is less harmful when taken orally than intravenously because, at physiological pH, it is ionized and therefore unlikely to penetrate the cellular membranes (Cohen, 1978;Cohen, 1975). Mice were not killed by intraperitoneal doses of 5,000 mg/kg of sodium fluoroacetate (Blake, et al, 1969) and no effects were seen after 100 mg/kg of trifluoroethanol ip daily for 18 days except for a failure to gain weight.…”
Section: Fluorinated Aliphatic Acidsmentioning
confidence: 99%